2021
DOI: 10.1186/s13643-021-01861-9
|View full text |Cite
|
Sign up to set email alerts
|

Dysphagia rehabilitation following acquired brain injury, including cerebral palsy, across the lifespan: a scoping review protocol

Abstract: Background Swallowing impairment (dysphagia) following brain injury can lead to life-threatening complications such as dehydration, aspiration pneumonia and acute choking episodes. In adult therapeutic practice, there is research and clinical evidence to support the use of swallowing exercises to improve swallowing physiology in dysphagia; however, the use of these exercises in treating children with dysphagia is largely unexplored. Fundamental questions remain regarding the feasibility and eff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Most reviewed case studies reported marked improvement of dyskinetic symptoms following DBS in at least 13 patients, this improvement was noted as being maintained over a year. The most frequently targeted area was the motor nucleus of the thalamus (specifically VIM/VO), for which a broad range of stimulation parameters have been applied (25-185 Hz, 120-500 μs, 1-8 V) [6,15,20]. DBS targeting the dentato-thalamo-cortical (DTC) pathway at its origin in the lateral cerebellar nucleus (LCN) has been shown to enhance motor recovery in a rodent model of cortical ischemia.…”
Section: Dbs For Post-stroke Dyskinesiamentioning
confidence: 99%
“…Most reviewed case studies reported marked improvement of dyskinetic symptoms following DBS in at least 13 patients, this improvement was noted as being maintained over a year. The most frequently targeted area was the motor nucleus of the thalamus (specifically VIM/VO), for which a broad range of stimulation parameters have been applied (25-185 Hz, 120-500 μs, 1-8 V) [6,15,20]. DBS targeting the dentato-thalamo-cortical (DTC) pathway at its origin in the lateral cerebellar nucleus (LCN) has been shown to enhance motor recovery in a rodent model of cortical ischemia.…”
Section: Dbs For Post-stroke Dyskinesiamentioning
confidence: 99%